Prenatal dietary exposure to chemicals and allergy or respiratory diseases in children in the EDEN mother–child cohort - Ghozal, Manel; Kadawathagedara, Manik; Delvert, Rosalie; Adel-Patient, Karine; Tafflet, Muriel; Annesi-Maesano, Isabella; Crépet, Amélie; Sirot, Véronique; Charles, Marie Aline; Heude, Barbara; de Lauzon-Guillain, Blandine (Environment international, 2023)
•Higher prenatal exposure to 74 chemicals was related to higher allergic rhinitis up to 8 years.•Higher prenatal exposure to acrylamide, 2 PAHS and 8 pesticides was related to higher wheezing up to 8 years.•Few associations were found between prenatal exposure to food chemicals and asthma, eczema or food allergy.•Prenatal dietary exposure to onechemical mixture was associated with higher risk of allergic rhinitis. Maternal exposure to food chemicals may increase the risk of allergy and respiratory disorders in offspring. We aimed to assess the association of prenatal dietary exposure to single chemicals and chemical mixtures with allergy or respiratory events reported before age 8 y in children. We included 1428 mother–child pairs enrolled in the EDEN mother–child cohort. Maternal dietary exposure to 209 chemicals and eight associated mixtures was investigated. Allergic and respiratory diseases (wheezing, asthma, allergic rhinitis, eczema and food allergy) were reported by parents between birth and age 8 y. Associations with the studied outcomes were evaluated with three approaches based on adjusted logistic regression, estimating odds ratios (ORs) and 95 % confidence intervals (CIs). First, food chemicals were considered individually, with correction for multiple testing. Second, chemicals selected by elastic net regression were considered simultaneously in a multiple exposure model. Third, predefined mixtures were introduced in the same adjusted logistic regression. Results are expressed as odds ratio (OR[95 % CI]). Prenatal single exposure to 74 food chemicals was associated with higher risk of allergic rhinitis. Prenatal single exposure to 11 chemicals was associated with higher risk of wheezing. In the multi-exposure approach, risk of wheezing was associated with the pesticides diazinon and triadimenol, and polycyclic aromatic hydrocarbon 5-methylchrysene. Phytoestrogen resveratrol was negatively associated with lower risk of both wheezing and allergic rhinitis, and mycotoxin monoacetoxyscirpenol was negatively associated with risk of eczema. Finally, a chemical mixture composed mainly of trace elements, furans and polycyclic aromatic hydrocarbons, was associated with higher risk of allergic rhinitis (1.33 [1.02;1.73]). Prenatal dietary exposure to chemicals was associated with risk of allergic rhinitis or wheezing up to age 8 y. A few chemicals were associated with other allergic and respiratory diseases. Larger prospective studies are needed to confirm these findings.